2013
DOI: 10.1039/c3cp51129d
|View full text |Cite
|
Sign up to set email alerts
|

π-Stacking effects on the EPR parameters of a prototypical DNA spin label

Abstract: The character and value of spin labels for probing environments like double-stranded DNA depends on the degree of change of the spin Hamiltonian parameters of the spin label induced by the environment. Herein we provide a systematic theoretical investigation of this issue, based on a density functional theory method applied to a spin labeled DNA model system, focusing on the dependence of the EPR properties of the spin label on the π stacking and hydrogen bonding that occur upon incorporating the spin label in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The correlation diagrams presented above signify the robustness of V N in representing the HFCCs of nitroxide radicals. It is worth mentioning that factors such as solvent polarity, noncovalent interactions, temperature, pH, and physical state of the sample can influence the HFCC values, which are not considered in the present study. Nevertheless, our study demonstrated the usefulness of V N values to capture subtle changes associated with the steric and electronic nature of the substituents in nitroxide radicals.…”
Section: Resultsmentioning
confidence: 99%
“…The correlation diagrams presented above signify the robustness of V N in representing the HFCCs of nitroxide radicals. It is worth mentioning that factors such as solvent polarity, noncovalent interactions, temperature, pH, and physical state of the sample can influence the HFCC values, which are not considered in the present study. Nevertheless, our study demonstrated the usefulness of V N values to capture subtle changes associated with the steric and electronic nature of the substituents in nitroxide radicals.…”
Section: Resultsmentioning
confidence: 99%
“…pep stacking interactions have been widely have been extensively reported in many areas such as organic synthesis [43,44], polymer chemistry [45e47], luminescent properties [48,49], the structures of biological macromolecules [50], and so on [51,52]. The nature of pep stacking interactions is formed by electron complementarity.…”
Section: Introductionmentioning
confidence: 99%